Efficient Removal of Ciprofloxacin from Water Using High-Surface-Area Activated Carbon Derived from Rice Husks: Adsorption Isotherms, Kinetics, and Thermodynamic Evaluation - Esra Demirdağ; Mehmet Ferit Demirel; Veysel Benek; Elif Doğru; Yunus Önal; Mehmet Hüseyin Alkan; Kadir Erol; İhsan Alacabey (Molecules)
Activated carbon is widely recognized as an effective material for removing pollutants, especially pharmaceutical residues, from water. In this study, high-surface-area activated carbon derived from rice husks (RHAC) was synthesized via KOH activation and used for the adsorption of ciprofloxacin, a widely used fluoroquinolone antibiotic. Its adsorption behavior was systematically investigated through batch experiments varying the pH, adsorbent dosage, contact time, initial concentration, and temperature. The RHAC exhibited a high surface area of 1539.7 m2/g and achieved a maximum adsorption capacity of 398.4 mg·g−1. The Freundlich isotherm best describes its adsorption equilibrium, suggesting multilayer adsorption on a heterogeneous surface. Kinetic modeling revealed that the adsorption process followed a pseudo second-order model (R2 = 0.9981), indicating chemisorption as the rate-limiting mechanism. Thermodynamic parameters (ΔH° = 6.61 kJ/mol, ΔG° < 0) confirmed that the process was endothermic and spontaneous. These findings demonstrate that RHAC is a highly efficient, low-cost, and sustainable adsorbent for removing ciprofloxacin from aqueous environments.